Net present value analysis of plant investment to add capacity - Gullickson, Travis R. (Kansas State University, 2008)
Providing a recommendation on whether to make a capacity expanding capital investment in an existing butter plant is the subject of this thesis. This is important as the success of this project will have a significant impact on the future profitability of Land O'Lakes and provide a significant home for its member's milk production. The dairy industry has undergone change over the past decades. Milk production has moved from the traditional production area of the Upper Midwest to drier, more arid areas such as California. This has led to milk price premiums in the Upper Midwest and since milk is the major input to butter manufacturing, it has become more attractive to produce butter in other areas such as California. Much of the data collected in review of the industry were obtained from the USDA. This data were used to describe the industry and focus on the number of butter plants over time, the milk productivity per cow, and the total milk production by state. It provides a clear picture of fewer bigger plants, more productive cows, and a dramatic shift in milk production to the West, primarily California. A Net Present Value (NPV) model is developed to analyze the trade off between the initial capital investment and less costly milk procurement over time. The model also considers maintenance costs, salvage values, plant startup delays, and a one time salvage value gain by shutting down an Upper Midwest plant. After the initial model is developed, sensitivity analysis is conducted, focusing on key variables such as demand growth, and the spread between California and Upper Midwest milk prices. The conclusion is that additional investment in California butter production would be profitable, earning a positive NPV and an Internal Rate of Return (IRR) greater than the Land O'Lakes cost of capital. The solution is robust as they remain the same even after modeling lower demand and smaller milk price differentials. Therefore, I recommend that Land O'Lakes move ahead with this capital investment.
Keywords: Investment Analysis; Land O'Lakes; Net Present Value; Butter Manufacturing; Agriculture, General (0473); Economics, Agricultural (0503); Economics, Finance (0508)